Continuous Professional Development of School Teachers: Extension, Possibilities and Alternatives: Exploring Opportunities for Continuous Professional Development in Education Teaching (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Professional development for teachers should be analogous to professional development for other professionals. Becoming an effective education teacher is a continuous process that stretches from pre-service experiences in undergraduate years to the end of a professional career.Science has a rapidly changing knowledge base and expanding relevance to societal issues, and teachers will need ongoing opportunities to build their understanding and ability. Teachers also must have opportunities to develop understanding of how students with diverse interests, abilities, and experiences make sense of scientific ideas and what a teacher does to support and guide all students. And teachers require the opportunity to study and engage in research on education teaching and learning, and to share with colleagues what they have learned.